PROFIL PENYELESAIAN SOAL MATERI FUNGSI KOMPOSISI KELAS X SMA NEGERI 1 SIGI DITINJAU DARI TIPE KEPRIBADIAN EXTROVERT DAN INTROVERT: Profile of Solving Function Composition Materials of Grade X Students of SMA Negeri 1 Sigi Type in Terms of The Extrovert and Introvert Personality - Hartina; Paloloang, Baharuddin; Rizal, Muh. (Universitas Tadulako, 2023)
The purpose of this study was to find out how the composition function in problem-solving profiles of class X students of SMA Negeri 1 Sigi in terms of extrovert and introvert personality types. This research is qualitative. The subjects of this study were 2 students of class X MIPA 3 at SMA Negeri 1 Sigi. Subjects were taken using the Myers-Briggs-Type Indicator personality test. The data validity technique used in this study is time triangulation. Data analysis technique with steps 1) data condensation, 2) data presentation and 3) concluding. The results showed that both extrovert and introvert subjects were capable of formulating solutions. using logical reasoning. The indicators of applying the introverted subject's strategy can explain clearly each step taken in solving the problem. Introvert subjects are more thorough and careful than extrovert subjects in solving problems. This is shown by the imprecise calculations carried out by the extrovert subject. In the indicators explaining the results of the completion, introvert subjects can conclude by proving the correctness of the results obtained, while extrovert subjects cannot write them down correctly.